An approach on the use of CAD-CAM technology for the manufacture of removable partial dentures - Pordeus, Mariana Domingues (2020)
The Removable Partial Denture (RPD) represents a specialty of great importance for Dentistry, being well indicated in many cases of Oral Rehabilitation. The purpose of this review was to investigate the use of CAD-CAM (computer aided design), as technologies for rapid updating and prototyping (RP) for the manufacture of PPRs. An electronic search was performed in the PubMed / MEDLINE, Web of Science, Cochrane Library and SciELO databases, according to the preferred report items for systematic analyzes and meta-analysis (PRISMA Statement) and was registered in the International Registry Prospective of Clinical Systematics (PROSPERO: CRD42020152197). A question about population, intervention, comparison, outcome (PICO) was \"How do CAD-CAM structures perform similarly to those manufactured by specific techniques?\" Clinical and in vitro studies were selected and analyzed selected and a total of 15 articles out of 358 were selected. A meta-analysis included clinical and in vitro studies based on the Mantel-Haenszel test with a 95% confidence interval (95% CI). For clinical studies, a quantitative analysis with a sample of 25 participants showed an average discrepancy between occlusal supports and niches of 184.91 m (95% CI: 152.6 m - 217.15 m) and heterogeneity (I2) of 0% , and considered the structures considered acceptable for the inheritance of the treatment. The predominant materials were Cobalt-Chromium (Co-Cr) and Polyetheretheretone (PEEK), the most recent being accepted for improved aesthetics. Quantitative data from in vitro studies revealed that the additive manufacturing technique (2,006 mm: 95% CI: -2,021 mm - 6,032 mm) was no different from the indirect technique (0.026 mm); (P = 0.329; random: I2: 94.34%). Conclude that clinical studies and in vitro research on planning and manufacturing of PPR infrastructures by CAD-CAM are still scarce. However, preliminary data can be adjusted and better aesthetic when compared to the conventional technique.